Bibliografiia russkoi zarubezhnoi literatury, 1918-1968 = Bibliography of Russian emigre literature, 1918-1968 - sostavitel' Liudmila A. Foster. (G. K. Hall, 1970)
Prefatory matter and table of contents in English.